Inorganic solid electrolyte ionic conductive composite current collector and manufacturing method and application thereof

By covering the inorganic solid electrolyte particles of the binder in the lithium-ion battery, forming a conductive composite liquid collector, the problem of deterioration of the interface between the inorganic solid electrolyte and the active substance in the lithium-ion battery is solved, and the density, durability and Safety significantly improves the cycle life and electrochemical performance of the battery.

CN119252933APending Publication Date: 2025-01-03SHENZHEN BTR NEW ENERGY TECH RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411392025.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

In lithium-ion batteries, the interface deterioration between the inorganic solid electrolyte and the positive electrode active substance leads to a decrease in electrical performance, and the content of binder has a significant impact on the battery performance and life. The existing dry electrode technology has problems of interface deterioration and insufficient safety.

Method used

By covering the binder film on the surface of the inorganic solid electrolyte particles, an inorganic solid electrolyte ion conductive composite liquid is formed, the binder content of the electrode sheet is increased, the interface between the inorganic solid electrolyte and the active substance is isolated, and the conductive surface is coated on the electrode surface. The agent is used to form a conductive network to enhance the acupuncture safety of the battery.

Benefits of technology

It effectively avoids lithium ion migration and interface deterioration problems, improves the density, durability and safety of lithium batteries, significantly improves the needle penetration rate of lithium ion batteries, extends the battery cycle life and maintains electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252933A_ABST
    Figure CN119252933A_ABST
Patent Text Reader

Abstract

The invention discloses an inorganic solid electrolyte ionic conductive composite current collector material as well as a preparation method and application thereof. The inorganic solid electrolyte ionic conductive composite current collector material comprises a current collector and a coating, the coating at least comprises an inorganic solid electrolyte and a binder; the binder wraps the surfaces of the particles of the inorganic solid electrolyte to form a coating film; and the coating uniformly covers or incompletely covers the surface of the current collector. The surface of the current collector is coated with the coating, so that the solid electrolyte and the positive electrode active material are effectively isolated, and the problem that lithium ions in the positive electrode active material are transferred into the inorganic solid electrolyte due to the concentration difference of the lithium ions in the positive electrode active material and the inorganic solid electrolyte is avoided; and the problem of interface deterioration caused by temperature rise in the use process is solved, so that the electrical performance of the lithium battery is deteriorated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to an inorganic solid electrolyte ion conductive composite current collector and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries (LIBs) have the advantages of high capacity, low cost and easy large-scale production, and are considered to be the most promising new generation of clean energy. In particular, lithium-ion batteries are widely used in electric vehicles, large-scale energy storage, aerospace and other fields due to their high energy density, low self-discharge, no memory effect and long cycle life. They play an important role in the fields of people's livelihood and military. Lithium-ion batteries are mainly composed of electrode sheets, electrolytes, diaphragms and shells. The most commonly used commercial production process of electrode sheets is to disperse electrode active materials, binders and conductive agents in N-methylpyrrolidone (NMP) solvent, stir and disperse them into a uniform slurry, and then use a coater to coat it on a metal foil current collector, and then use the hot air oven of the coater to dry the slurry to obtain an electrode sheet. The usual production method is a wet coating process, that is, a solvent and a powder material are mixed to prepare a slurry, and then a dry electrode is prepared by coating, drying, solvent recovery and other processes. The dry electrode manufacturing process simplifies the process and equipment, consumes no solvents, reduces energy consumption and carbon emissions, and is an environmentally friendly solution. At present, the dry electrode technology uses the fibrillation of the binder polytetrafluoroethylene (PTFE) to achieve the bonding of active materials, conductive agents and foils.

[0003] On the other hand, inorganic solid electrolytes are increasingly used in lithium-ion batteries. They can be coated on the surface of the positive electrode and / or the negative electrode, or on the surface of the diaphragm, and have different degrees of improvement on battery performance. However, when the inorganic solid electrolyte is coated on the surface of the positive electrode, the concentration of lithium ions in the positive electrode active material is higher than that of the inorganic solid electrolyte, resulting in the transfer of lithium ions in the positive electrode active material to the inorganic solid electrolyte. At the same time, the degradation of the positive electrode-LATP interface and the formation of secondary phases at high temperatures lead to deterioration of electrical performance.

[0004] Furthermore, in the positive electrode material of lithium batteries, the content of the binder has an important influence on the performance of the positive electrode material and directly affects the performance and life of the battery. The proportion of the binder is usually between 1% and 5%. A higher binder content can improve the density and durability of the positive electrode material, but too high a binder content will reduce the power and energy density of the battery. Therefore, in actual production, the binder content is usually 1-3%.

[0005] Based on this, the present invention provides an inorganic solid electrolyte ion conductive composite current collector on the basis of the prior art. By coating a layer of binder film on the surface of the inorganic solid electrolyte particles, the inorganic solid electrolyte is isolated from the active material of the electrode, thereby avoiding the problem of interface deterioration between the two. At the same time, by increasing the content of the binder in the electrode sheet, not only the density and durability of the positive electrode material are improved, but also the acupuncture safety of the lithium battery is greatly improved. The preparation method of the current collector is simple and low in cost, and is suitable for large-scale promotion and application. Summary of the invention

[0006] In order to solve the above-mentioned technical problems, the present invention provides an inorganic solid electrolyte ion conductive composite current collector and its preparation method and application; the inorganic solid electrolyte particles are coated with a binder and then coated on the surface of the current collector to solve the interface problem between the inorganic solid electrolyte and the active substance, and at the same time improve the acupuncture safety of the lithium battery.

[0007] In order to achieve the above-mentioned purpose, the present invention provides an inorganic solid electrolyte ion conductive composite current collector material, comprising a current collector and a coating; the coating comprises at least an inorganic solid electrolyte and a binder; the binder is wrapped around the surface of the inorganic solid electrolyte particles to form a coating film; the coating uniformly covers or incompletely covers the surface of the current collector.

[0008] Preferably, the coating has a thickness of 0.05-10 μm.

[0009] Preferably, the coating film has a thickness of 100 to 1000 nm.

[0010] Preferably, in the coating, the content of the binder is 5 to 50 wt %.

[0011] Preferably, the inorganic solid electrolyte includes any one of LLTO, LLZO, LAGTP or LATP.

[0012] Preferably, the binder is any one of styrene-butadiene rubber, carboxymethyl cellulose, polyacrylic acid and polyacrylonitrile.

[0013] Preferably, the current collector material is aluminum foil.

[0014] Preferably, the coating further contains a conductive agent, which is evenly dispersed in the binder to form a conductive network.

[0015] Preferably, the conductive agent is at least one of Super-P (SP), acetylene black (AB), Ketjen black (KB), carbon fiber (VGCF), carbon nanotube (CNT), and graphene.

[0016] Preferably, in terms of mass percentage, the contents of the components in the coating are: 30-95% of the inorganic solid electrolyte, 5-50% of the binder, and 0-10% of the conductive agent.

[0017] Preferably, when the coating layer contains the conductive agent, the coating layer may completely or incompletely cover the surface of the current collector.

[0018] Preferably, when the coating layer does not contain the conductive agent, the coating layer does not completely cover the surface of the current collector, and the coating layer regularly exposes metal sites of the current collector.

[0019] As another object of the invention, the present invention also provides a method for preparing the above-mentioned inorganic solid electrolyte ion conductive composite current collector material, comprising:

[0020] S1. Providing a binder solution; dissolving the binder in a solvent to form a binder solution;

[0021] S2. The inorganic solid electrolyte is added to the binder solution and dispersed to form a dispersed mixture;

[0022] S3. The dispersed mixed liquid is first dried and then heat-treated to remove the solvent to form a powdery substance, namely an inorganic solid electrolyte-binder, wherein the inorganic solid electrolyte-binder is coated on the surface of the inorganic solid electrolyte particles;

[0023] S4. After mixing the inorganic solid electrolyte-binder, polyacrylic acid and / or conductive agent, coating or printing on the surface of the current collector, the coating is formed after drying.

[0024] Preferably, in S1, the solvent includes but is not limited to deionized water, NMP, ethanol, acetone, N,N-dimethylformamide (DMF) and the like.

[0025] Preferably, in S3, the drying comprises heating at 50-100° C. for 6-24 hours under vacuum conditions.

[0026] Preferably, the heat treatment comprises heating to 200-300° C. at a heating rate of 1-3° C. / min in an inert gas atmosphere; and then keeping the temperature for 1-3 hours.

[0027] As one of the aspects of the invention, the present invention also provides a positive electrode sheet, which is prepared by using the above-mentioned inorganic solid electrolyte ion conductive composite current collector as a matrix material and coating an active positive electrode material on the surface of the matrix material; the positive electrode material is any one of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide and lithium iron phosphate.

[0028] Furthermore, the positive electrode sheet, the negative electrode sheet and the separator are assembled to obtain a lithium electronic battery.

[0029] Based on the above technical scheme, the present invention provides a composite current collector and coats a coating on the surface of the current collector to effectively isolate the solid electrolyte and the positive electrode active material, thereby avoiding the problem of lithium ions in the positive electrode active material being transferred to the inorganic solid electrolyte due to the concentration difference between the positive electrode active material and the lithium ions in the inorganic solid electrolyte, and the problem of interface deterioration caused by the increase in temperature during use, which in turn leads to deterioration of the electrical performance of the lithium battery.

[0030] At the same time, a solution to the safety performance of lithium-ion battery needle puncture, an inorganic solid electrolyte ion conductive composite current collector and a lithium-ion battery are provided. The lithium-ion battery provided by the present invention has a positive electrode composed of an inorganic solid electrolyte ion conductive composite current collector and a positive electrode material, and a negative electrode composed of a copper foil and a negative electrode material. The lithium-ion battery provided by the present invention can not only solve the interface problem between the inorganic solid electrolyte and the active material, but also improve the needle puncture pass rate of the lithium-ion battery by more than 50% compared with conventional batteries.

[0031] The present invention avoids the problem of lithium ion migration and interface deterioration caused by the contact between the inorganic solid electrolyte and the active material by coating the organic polymer on the surface of the inorganic solid electrolyte. In the carbon-free composite cathode, it is difficult to reconcile electron migration and interface protection, which limits the power performance of the lithium-ion battery. Based on this, the present invention applies the method of repairing the inorganic coating with a polymer to the positive electrode material particles to ensure that the electron migration is not affected. Compensate for the problem of interface deterioration in the existing positive electrode material. Specifically, interface degradation is mainly caused by electrochemically driven parasitic reactions and chemical mechanically induced contact losses in the composite cathode. The present invention reduces parasitic reactions on the interface by uniformly covering the surface of the positive electrode material with a layer of polymer coating; on the other hand, from the perspective of preventing cathode chemical mechanical failure, conventional inorganic solid electrolyte positive electrode materials can effectively maintain the microstructural integrity of the particles, thereby extending the cycle life of the battery. At the same time, it is also found that serious side reactions are still an important cause of battery capacity loss. Therefore, in the organic polymer-coated inorganic solid electrolyte coating scheme of the present invention, the organic-inorganic coating scheme is conducive to uniform coverage of the coating, avoiding direct contact between the uncovered area of ​​the inorganic solid electrolyte coating and the positive electrode particles. The inorganic solid electrolyte has rapid ion transfer capability, and SP provides extended electronic contact between the interconnected inorganic solid electrolyte and the positive electrode active material particles. Therefore, the coating also has both ionic conductivity and electronic insulation.

[0032] Taking LATP as an example, the organic polymer-coated LATP coating ensures rapid interfacial Lit transfer and has high oxidation resistance, while the organic polymer makes up for the defects in the LATP coating. By adding SP, an extended electron permeation path is provided between the interconnected LATP, organic polymer and active material particles. Therefore, the battery prepared by the organic-inorganic coating method exhibits competitive electrochemical performance in terms of capacity retention, with a 1C / 3C cycle retention rate of 100% after 1,000 cycles, which is eight percentage points higher than the benchmark. Therefore, the key to the improvement made by the present invention on the basis of the prior art lies in the uniformity and functionality of the coating, which can significantly suppress interfacial parasitic reactions while ensuring the essential electron penetration.

[0033] Based on the above analysis, the lithium-ion battery made of the composite current collector formed by the polymer-wrapped LATP coating provided by the present invention can exhibit more stable electrical performance and longer cycle life.

[0034] Beneficial technical effects obtained by the present invention:

[0035] 1. The present invention avoids the problem of lithium ion migration and interface deterioration caused by the contact between the inorganic solid electrolyte and the active material by coating the binder on the surface of the inorganic solid electrolyte, and has almost no effect on the battery power and energy density.

[0036] 2. The puncture rate of the lithium-ion battery assembled by the technical solution of the present invention is 83.3%, which is increased by more than 50%, while the puncture rate of the conventional lithium-ion battery is 0%. This performance improvement is mainly due to the fact that the coated LATP has a certain electronic insulation and is in closer contact with the current collector. When the steel needle pierces the battery separator during the puncture test, the coated LATP coating cuts off the direct contact between the positive and negative electrodes, avoiding the probability of internal short circuits and improving the safety of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is a cycle comparison diagram of full batteries assembled for Example 1, Comparative Example 1 and Comparative Example 2 of the present invention at room temperature.

[0038] Figure 2 This is a cycle comparison diagram of full batteries assembled for Example 1, Comparative Example 1 and Comparative Example 2 of the present invention at a temperature of 45°C.

[0039] Figure 3 This is a simulation test diagram of the acupuncture safety test method adopted by the present invention. DETAILED DESCRIPTION

[0040] In view of the defects of the prior art, the present invention proposes a sodium ion secondary battery positive electrode active material and provides a preparation method thereof. The specific technical scheme of the present invention is described in detail below through specific implementation methods. Obviously, the described embodiments are part of the embodiments of the present invention, not all of them. In order to describe concisely, it is impossible for this specification to describe in detail all the features of the actual implementation methods. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] It should be noted that, unless otherwise defined, the technical terms or scientific terms used in this specification should be known to those skilled in the art of this application.

[0042] The technical solution of the present invention is described in detail below through specific implementation methods.

[0043] Example 1

[0044] First, polyacrylonitrile (PAN) was dissolved in N,N-dimethylformamide (DMF) solvent at a mass ratio of 1:10 to form a PAN solution.

[0045] Subsequently, LATP powder was added to the PAN solution and stirred at 25° C. for 2 h to form a dispersion; wherein the mass ratio of PAN to LATP was 2:100.

[0046] Then, the dispersion was heated at 60 °C for 10 h in vacuum to eliminate the deionized water solvent, and then the obtained powder was heat-treated in a tube furnace with an argon flow rate of 80 sccm, a heat treatment temperature of 250 °C, a holding time of 1 h, and a heating rate of 2 °C.

[0047] Then, the organic polymer-coated inorganic solid electrolyte LATP-PAN was obtained by natural cooling; the D10 of LATP-PAN was 0.05 μm, D50 was 0.6 μm, D90 was 1.6 μm, and the electronic conductivity was 7.0*10 -5 S cm -1 (20KN), ionic conductivity is 5.7*10 -5 S cm -1 ; The thickness of the coating is 100~1000nm.

[0048] Finally, the above LATP-PAN is mixed with SP and PAA in a ratio of 95.0:2.0:3.0 and stirred evenly, and the mixture is evenly coated or printed on the surface of the current collector aluminum foil. After drying, the inorganic solid electrolyte ion conductive composite current collector material AL-L is obtained, and the coating thickness is 1-2 μm; then the NCM523 nickel cobalt manganese oxide ternary material is coated on the surface, and the negative electrode sheet is made of graphite material. According to the conventional lithium ion battery process, a soft-pack laminated battery with a nominal capacity of 2.0 Ah is manufactured, and a cycle life test is performed. The test results are shown in Table 1. Figure 1 and Figure 2 .

[0049] In the PAN-coated LATP coating solution provided in this embodiment, the organic-inorganic composite treatment is conducive to uniform coating coverage, avoiding direct contact between the uncovered area of ​​the LATP coating and the positive electrode particles; the inorganic solid electrolyte LATP has a fast ion transfer capability, and SP provides extended electronic contact between the interconnected LATP and the positive electrode active material particles. Therefore, the lithium-ion battery prepared by this method exhibits more stable electrical performance and longer cycle life.

[0050] Example 2

[0051] The only difference between this embodiment and embodiment 1 is that in the organic polymer-coated inorganic solid electrolyte LATP-PAN, the mass ratio of PAN to LATP is 5:100.

[0052] Example 3

[0053] The only difference between this embodiment and embodiment 1 is that in the organic polymer-coated inorganic solid electrolyte LATP-PAN, the mass ratio of PAN to LATP is 0.4:100.

[0054] Example 4

[0055] The difference between this embodiment and embodiment 1 is that SP is not included; specifically, the LATP-PAN and PAA prepared in embodiment 1 are mixed and stirred in a ratio of 97.0:3.0, and are evenly coated on the surface of the current collector aluminum foil without completely covering it, and the aluminum foil sites arranged in an array are exposed in the coating; after drying, the inorganic solid electrolyte ion conductive composite current collector material AL-L is obtained, and the coating thickness is 1 to 2 μm; then the NCM523 nickel cobalt manganese oxide ternary material is coated on its surface, and the negative electrode sheet is made of graphite material, and a soft-pack laminated battery with a nominal capacity of 2.0 Ah is manufactured according to a conventional lithium-ion battery process, and a cycle life test is carried out.

[0056] Comparative Example 1

[0057] In this comparative example, aluminum foil is used as the current collector, and NCM523 nickel cobalt manganese oxide ternary material is directly coated on the surface of the current collector, excluding LATP. Other processes are the same as in Example 1 to form a positive electrode sheet; graphite material is used as the negative electrode sheet, and a soft-pack laminated battery with a nominal capacity of 2.0 Ah is manufactured according to a conventional lithium-ion battery process, and a cycle life test is performed. The test results of the full battery performance parameters are shown in Table 1.

[0058] Comparative Example 2

[0059] In this comparative example, aluminum foil is used as the current collector, and LATP mixed glue (the mass ratio of LATP to SP and PAA is 95:2:3) is directly coated on the surface of the current collector to form a coating, the thickness of the coating and the content of LATP are the same as those in Example 1, thereby forming a composite current collector, and then NCM523 nickel cobalt manganese oxide ternary material is directly coated on the surface of the composite current collector to form a positive electrode sheet, and the amount of LATP added and the coating thickness are the same as those in Example 1; graphite material is used as the negative electrode sheet, and a soft-pack laminated battery with a nominal capacity of 2.0Ah is manufactured according to a conventional lithium-ion battery process, and a cycle life test is performed. The test results of the full battery performance parameters are shown in Table 1.

[0060] Comparative Example 3

[0061] The only difference between this comparative example and Example 4 is that LATP-PAN and PAA are mixed in a ratio of 97.0:3.0, stirred evenly, and then coated on the surface of the aluminum foil to form a full-coverage coating.

[0062] Comparative Example 4

[0063] The difference between this comparative example and Example 2 is that LATP is not coated, but a slurry of PAN and LATP mixed evenly is directly coated on the surface of the current collector to form a coating; in the coating, the content of the binder is 4.86% (the sum of the amount of PAN coated with LATP in Example 2 and the binder content in the coating of Example 2). The thickness of the coating and the content of LATP are the same as those in Example 1, and then a composite current collector is formed, and then NCM523 nickel cobalt manganese oxide ternary material is directly coated on the surface of the composite current collector to form a positive electrode sheet, and the amount of LATP added and the thickness of the coating are the same as those in Example 1; using graphite material as the negative electrode sheet, a soft-pack laminated battery with a nominal capacity of 2.0Ah is manufactured according to a conventional lithium-ion battery process, and a cycle life test is performed. The test results of the full battery performance parameters are shown in Table 1.

[0064] Table 1 Full battery performance parameter test results of the embodiment and the comparative example

[0065]

[0066] The positive electrode material of Example 1, Comparative Example 1 and Comparative Example 2 is the surface of the current collector material coated with NCM523, and the negative electrode material is a laminated soft-pack battery prepared from graphite, the difference being that the current collector coating material is different. Comparative Example 1 does not add LATP, and the resistivity of the positive electrode sheet is significantly lower than that of the positive electrode sheet of Example 1 and Comparative Example 2 to which LATP is added. The only difference between Example 1 and Comparative Example 2 is that the particles of LATP in Example 1 are coated with PAN and then coated on the surface of the aluminum foil, while Comparative Example 2 directly coats LATP on the surface of the aluminum foil to form a composite current collector, and the resistivity of the positive electrode sheet of Example 1 is slightly higher than that of Comparative Example 2.

[0067] The cycle stability of the embodiments and comparative examples was further analyzed. Figure 1 The full-battery room temperature cycle diagram of Example 1, Comparative Example 1 and Comparative Example 2, combined with the test results of Table 1, when the 1C charge and 3C discharge cycles are 750 weeks, the capacity retention rate of Example 1 is still 101%, the initial capacity is 1889mAh, and the capacity at the 750th week is 1902mAh. The reason for the increase in capacity is that the electronic conductivity of LATP itself is poor, and the electronic conductivity is slightly reduced after being coated with organic polymers. The ohmic impedance of the full battery increases, the battery ohmic polarization increases, and the initial capacity decreases. However, as the cycle progresses, the battery is gradually activated, the contact between particles becomes closer, the ohmic polarization decreases, the temperature rises slightly, the lithium ion migration speed increases, and the battery cycle retention rate increases. Figure 2 As shown, in a high temperature environment of 45°C, the inside of the battery is quickly activated, the defects between the particles are filled, and there is no downward trend in the cycle of Example 1. The cycle curve is stable and the retention rate is significantly better than that of Comparative Examples 1 and 2; wherein, Comparative Example 1 is a conventional aluminum foil, and a battery without LATP coating. The retention rate of this battery rises slightly in the first 50 cycles and then drops immediately, while Comparative Example 2 is a lithium ion laminate soft-pack battery made by the same process as Example 1, in which LATP is not coated with an organic polymer and an aluminum foil primer is applied, and then the composite current collector is positively coated and the battery is made according to the same process as Example 1. LATP provides ion conductivity, and its cycle performance is better than that of Comparative Example 1. However, the problem of interface degradation caused by the concentration difference between the positive electrode active material and the lithium ions in the inorganic solid electrolyte during the cycle gradually becomes prominent, and the long-term cycle retention rate is significantly lower than that of Example 1.

[0068] Finally, acupuncture safety test experiments were carried out on the embodiments and comparative examples to verify the safety of acupuncture.

[0069] See also Figure 3 This is a simulation test diagram of the needle puncture safety test method, which includes positive electrode sheet-diaphragm-negative electrode sheet in sequence. The positive electrode sheet includes: aluminum foil coated with inorganic solid electrolyte on both sides, and positive electrode material is coated on the inorganic solid electrolyte layer; the negative electrode includes: copper foil coated with negative electrode material on both sides. During the test, the steel needle passes through the positive electrode sheet, diaphragm and negative electrode sheet in sequence.

[0070] The test steps include: the steel needle first pierces the positive electrode sheet, and the inorganic solid electrolyte on the surface of the aluminum foil separates the diaphragm, reducing the probability of the aluminum foil directly contacting the negative electrode sheet. A total of 12 pieces were tested.

[0071] The surface of the aluminum foil in Example 1 is coated with LATP-PAN, the surface of the aluminum foil in Comparative Example 1 is not coated with any substance, and the surface of the aluminum foil in Comparative Example 2 is directly coated with LATP.

[0072] Test results: In Example 1, 10 pcs of batteries were qualified without fire or explosion, and the pass rate of needle puncture was increased by 83.3%. In Comparative Example 1, all 12 pcs of batteries caught fire and exploded, and the pass rate of needle puncture was 0%. In Comparative Example 2, 9 pcs of batteries were qualified without fire or explosion, and the pass rate of needle puncture was 75%. This shows that after the current collector is coated with LATP, the battery safety performance is significantly improved.

[0073] The above are only preferred embodiments of the present invention, which do not limit the protection scope of the present invention. For those skilled in the art, the present invention may have various modifications and changes. Within the spirit and principle of the present invention, changes, modifications, replacements, integrations and parameter changes to these embodiments by conventional substitutions or capable of achieving the same functions without departing from the principles and spirit of the present invention all fall within the protection scope of the present invention.

Claims

1. An inorganic solid electrolyte ion conductive composite current collector material, characterized in that: including current collector and coating; The coating at least includes an inorganic solid electrolyte and a binder; The binder is wrapped around the surface of the inorganic solid electrolyte particles to form a coating film; The coating layer uniformly covers or incompletely covers the surface of the current collector.

2. The inorganic solid electrolyte ion conductive composite current collector material according to claim 1, characterized in that: The thickness of the coating is 0.05 to 10 μm; The coating film has a thickness of 100 to 1000 nm.

3. The inorganic solid electrolyte ion conductive composite current collector material according to claim 1, characterized in that: In the coating, the content of the binder is 5 to 50 wt%.

4. The inorganic solid electrolyte ion conductive composite current collector material according to claim 1, characterized in that: The inorganic solid electrolyte includes any one of LLTO, LLZO, LAGTP or LATP; The binder is any one of styrene-butadiene rubber, carboxymethyl cellulose, polyacrylic acid, and polyacrylonitrile; The current collector material is aluminum foil.

5. The inorganic solid electrolyte ion conductive composite current collector material according to any one of claims 1 to 4, characterized in that: The coating also contains a conductive agent, which is uniformly dispersed in the binder to form a conductive network; and / or the conductive agent is at least one of Super-P, acetylene black and Ketjen black, carbon fiber, carbon nanotubes, and graphene.

6. The inorganic solid electrolyte ion conductive composite current collector material according to claim 5, characterized in that: In terms of mass percentage, the contents of the components in the coating are: 30-95% of the inorganic solid electrolyte, 5-50% of the binder, and 0-10% of the conductive agent; And / or, when the coating contains the conductive agent, the coating may completely or incompletely cover the surface of the current collector; And / or, when the coating layer does not contain the conductive agent, the coating layer does not completely cover the surface of the current collector, and the coating layer regularly exposes metal sites of the current collector.

7. A method for preparing the inorganic solid electrolyte ion conductive composite current collector material according to any one of claims 1 to 6, characterized in that: The specific steps include S1. Providing a binder solution; dissolving the binder in a solvent to form a binder solution; S2. The inorganic solid electrolyte is added to the binder solution and dispersed to form a dispersed mixture; S3. The dispersed mixed liquid is first dried and then heat-treated to remove the solvent to form a powdery substance, namely an inorganic solid electrolyte-binder, wherein the inorganic solid electrolyte-binder is coated on the surface of the inorganic solid electrolyte particles; S4. After mixing the inorganic solid electrolyte-binder, polyacrylic acid and / or conductive agent, coating or printing on the surface of the current collector, and forming a coating on the surface of the current collector after drying, the composite current collector is obtained.

8. The method according to claim 7, characterized in that In S1, the solvent may be any one of deionized water, NMP, ethanol, acetone, and N,N-dimethylformamide; In S3, the drying includes heating at 50-100° C. for 6-24 hours under vacuum conditions; The heat treatment comprises heating the material to 200-300° C. at a heating rate of 1-3° C. / min in an inert gas atmosphere, and then keeping the temperature for 1-3 hours.

9. A positive electrode sheet, characterized in that: The inorganic solid electrolyte ion conductive composite current collector according to any one of claims 1 to 6 is used as a base material, and an active positive electrode material is coated on the surface of the base material to prepare it; the positive electrode material is any one of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide and lithium iron phosphate.

10. A lithium ion battery, characterized in that: The invention is assembled from at least the positive electrode sheet as claimed in claim 9, and a negative electrode sheet and a separator.